Challenges elementary teachers face when teaching military-connected students - Mittelberg, Julia A. (Kansas State University, 2014)
Military-connected students are a highly mobile population who undergo a great deal of stress in their lives. These factors can overflow into life in the elementary classroom, causing challenges for teachers. This study looked at the percieved challenges elementary classroom teachers face when working with military-connected students in one public school district with schools located on a military base and other schools near it. A Likert-type survey of questions was created and administered to teachers using an online survey tool. The survey was sent to elementary teachers working in schools in one public school district in the Midwestern United States with a garnered response rate of 42.2% (n=68). The schools in the district were located in a city near and on a military base. The study used exploratory factor analysis, descriptive statistics, independent samples t-tests, an ANOVA, and step-wise regression analysis procedures to answer the research questions regarding the challenges teachers face when working with military-connected students. The results of the study indicated that the number of years a teacher has been teaching influences their perceptions of challenges regarding military-connected students. In addition, teachers indicated that helping students catch up academically, supporting them emotionally, and family/parent issues are the top challenges when working with elementary military-connected students.
Keywords: Elementary education; Elementary Education (0524)